Participants at the 1986 y-Walk finish line - Brock, Trish (photographer):::Creator::::::::::::
Negative shows men and women at the 1986 y-Walk's finish line. They are posing around a sign that reads: "Free parking 1 block north on Third." Two of the women are leaning on the sign as if tired, and the finish line is in the background. Some of them are carrying balloons and some are wearing tee shirts that read: "Walk for women. YWCA1986."